Testing risk and protective factor assumptions in the Icelandic model of adolescent substance use prevention. Issue 3 (12th January 2021) - Kristjansson, Alfgeir L; Lilly, Christa L; Thorisdottir, Ingibjorg E; Allegrante, John P; Mann, Michael J; Sigfusson, Jon; Soriano, Humberto E; Sigfusdottir, Inga Dora
Abstract: Iceland has witnessed a dramatic decline in adolescent substance use that may be partly the result of efforts related to the Icelandic prevention model (IPM). We sought to test risk and protective factor assumptions of the IPM using a prospective cohort study with 12 months separating baseline from follow-up. Participants were students in grades 8 and 9 in the national Icelandic school system enrolled in the spring of 2018 and 2019 ( N =2165). Participants self-reported their experiences of cigarette smoking, alcohol consumption, and cannabis use and seven risk and protective factors. Analyses were conducted with generalized linear modeling with extension to general estimating equations with correlated outcomes data. Both individual main-effects models and collective models including all main-effects were tested. Out of 28 individual main-effects models, 23 produced findings consistent with study premises ( P <0.05). Multiple main-effects models largely sustained the findings of the individual main-effects models. Findings support the assumption that the risk and protective factors commonly emphasized in the IPM are associated with the four different substance use outcomes in the hypothesized direction. Communities that plan to implement the IPM among adolescents might consider these factors in their work.